A safe and reliable neutralization assay based on pseudovirus to measure neutralizing antibody titer against poliovirus. Issue 12 (29th August 2017) - Liu, Shaohua; Song, Dongmei; Bai, Han; Lu, Weiwei; Dai, Xinxian; Hao, Chunsheng; Zhang, Zhongyang; Guo, Huijie; Zhang, Yue; Li, Xiuling
Abstract : With the promotion of inactivated poliomyelitis vaccine (IPV) and live attenuated oral poliomyelitis vaccine (OPV), the global reported cases of poliomyelitis have reduced sharply from 0.35 million in 1988 to 74 in 2015. The Polio Eradication & Endgame Strategic Plan published by WHO in 2013 included the strategy of implementation of poliovirus safe handling and containment measures to minimize the risks of facility‐associated reintroduction of virus into the polio‐free community to prevent the re‐import of poliovirus. Toward this strategy, we produced replication‐incompetent pseudovirus of poliovirus type 1, 2, 3 attenuated strains by constructing poliovirus capsid expression vectors and poliovirus replicon then transfecting HEK293T cells and developed a pseudovirus‐based neutralization assay (pNA) to determine neutralizing antibody titer which is more secure, time‐saving and reliable than conventional neutralization assay (cNA). By using anti‐poliovirus rat serum, we demonstrated excellent correlation between neutralizing antibody titers measured by cNA and pNA. It was concluded that pNA can be a potential alternative to replace cNA as a safe and time‐saving system for titer determination after live poliovirus's safekeeping.